PENEGAKAN HUKUM TERHADAP PENGEDARAN OBAT-OBATAN YANG TIDAK MEMILIKI IZIN EDAR PADA MASA PANDEMI COVID 19 - Tantra Hadimulya; Efridani Lubis; Muhammad Fahruddin (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2020)
Lina Marlena, 1220160040, Law Enforcement Against Circulation Of Drugs That Do Not Have ACirculation Permit During The Covid 19 Pandemic. Faculty of Law, Universitas Islam Assyafi’iyah, 2020. The purpose of this study is to determine law enforcement efforts without adistribution permit during the Covid 19 pandemic. This research uses a juridical-empirical researchmethod, a problem approach based on applicable laws and regulations, then touches on legalprinciples and facts of events. that happens on the field. The results of the study can be concludedthat someone can be said to have carried out the act of circulating illegal drugs if they violate articles196-197 of Law No. 36 of 2009 concerning Health. Meanwhile, corporations that carry out illegal drug distribution are charged under Article 201 of the Health Law and also for law enforcement, forperpetrators who have circulated illegal drugs, there are several sanctions, namely for criminal sanctions the perpetrator can be subjected to articles in accordance with the health law. , and forcivil sanctions the perpetrator is responsible for providing compensation for damages or losses to consumers as a result of consuming goods, and finally administrative sanctions in the form of verbal warnings, revocation of business licenses, and imposition of disciplinary penalties based onprevailing laws and regulations.